HYDROLOGICAL METHOD DEFINITION OF DESERTIFICATION BORDER (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Desertification, as a natural phenomenon, is stipulated by interaction of numerous factors. The article undertakes the attempt of defining the upper border of the desertification territory by hydrological methods. For desertification upper borders the altitude of precipitation and total vaporization crossing is admitted, and for the upper territory border, which is under the desertification danger is the altitude of precipitation and evaporation crossing. The above mentioned climatic and hydrologic methods not only highlight the regularities of spatial time of desertification allocation, but also give forecast possibilities.
Keywords: desertification territory; hydrologic methods; evaporation crossing